Innovation in the development of a maternity warm massage belt for reducing back pain intensity in working pregnant women - Putri, Poppy Siska; Ningsih, Sari Widya; Syafitasari, Juanda (Science Midwifery, 2024)
About 70% of pregnant women experience back pain, and working pregnant women are often very active. Persistent back pain can affect their quality of life, disrupt daily activities, lower work performance, and even cause trauma in future pregnancies. Currently, maternity belts do not include features such as back support, heating, massage, or an attractive design. This study aims to develop a maternity warm massage belt that can reduce the intensity of back pain. This research uses Research and Development (R&D) with three stages: analysis, development, and product testing. The quasi-experiment design includes a one-group pretest-posttest with 30 respondents selected through purposive sampling from July to September 2024 in the Puskesmas Sidomulyo area. In the first stage, feedback from 5 pregnant women indicated a desire for a belt with back support, heating, massage, and an appealing design. The second stage produced a maternity warm massage belt that met these expectations, with 92% of pregnant women finding it comfortable to use. The third stage of testing showed a reduction in back pain from 4,97 to 3, with a p-value of 0.000, indicating that the maternity warm massage belt effectively reduces back pain intensity. The maternity warm massage belt is effective in reducing back pain in pregnant women and could be an innovative product for further development.